ASUHAN KEPERAWATAN GERONTIK PADA PASIEN OSTEOPOROSISDENGAN MASALAH KEPERWATAN NYERI KRONIS MENGGUNAKAN TERAPI SENAM OSTEOPOROSIS DI UPT PSTW JOMBANG: GERONTIC NURSING CARE FOR OSTEOPOROSIS PATIENTS WITH CHRONIC PAIN NURSING PROBLEMS USING OSTEOPOROSIS EXERCISE THERAPY AT UPT PSTW JOMBANG - Muhammad Ibnu; Sugiarto, Kresna Bagus; Effendi, Zainudin (LPPM STIKes Bahrul Ulum Jombang, 2024)
Elderly people who experience musculoskeletal pain include elderly people with a history of gout, rheumatism, osteoporosis, osteoarthritis, lower back pain and muscle pain. There have been many methods used to overcome this pain, such as drinking warm water and taking pain medication, but these have not provided optimal results. Implement Gerontik Nursing Care for Osteoporosis Patients With Chronic Pain Nursin Problems at UPT PSTW Jombang. The design of this research is a case study using 2 osteoporosis clients with chronic pain nursing problems, who received nursing care for 7 consecutive days using an intervention, namely Osteoporosis Gymnastics therapy. The results of the study showed that the problem of chronic pain by providing Osteoporosis Exercise therapy, the problem was resolved in reducing the pain level of the elderly. Osteoporosis Exercise Therapy can help reduce pain and provide comfort to the elderly, this therapy is carried out for 7 days.